1983
DOI: 10.7164/antibiotics.36.1
|View full text |Cite
|
Sign up to set email alerts
|

A new aminoglycoside antibiotic G-367 S1, 2'-N-formylsisomicin fermentation, isolation and characterization.

Abstract: A new aminoglycoside antibiotic, G-367 S1 (2'-N-formylsisomicin, C20H37N5O8) produced by a rare actinomycetes, Dactylosporangium thailandense G-367 (FERM-P 4840) has been isolated by column chromatography on a cation-exchange resin. G-367 S1 is active against Gram-positive and Gram-negative bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…These observations on the influence of amide formation at the 2′-position are consistent with the prior literature describing other 2′-amides. Thus, it has been reported that the 2′- N -glycinamide derivatives of simple aminoalkyl 2,6-diamino-α- d -glucopyranosides, and of fortimicin B, retain antibacterial activity as does 2′-formamido sisomicin. …”
Section: Resultsmentioning
confidence: 99%
“…These observations on the influence of amide formation at the 2′-position are consistent with the prior literature describing other 2′-amides. Thus, it has been reported that the 2′- N -glycinamide derivatives of simple aminoalkyl 2,6-diamino-α- d -glucopyranosides, and of fortimicin B, retain antibacterial activity as does 2′-formamido sisomicin. …”
Section: Resultsmentioning
confidence: 99%
“…4,5 To reduce the incidence of graft infection, the development of prosthetic grafts that are resistant to infection has been anticipated. [6][7][8] Sisomicin (SISO) is used for prevention of postoperative infections [9][10][11] because it shows excellent antibacterial activities not only against Pseudomonas aeruginosa but also against staphylococci, including Staphylococcus aureus and Staphylococcus epidermidis, two of the major causative bacteria in graft infection. Fibrin glue (FG), which was developed as a tissue adhesive, is used for prevention of bleeding and sutural insufficiency in surgery at various sites.…”
Section: Introductionmentioning
confidence: 99%